Psychological impact of the COVID-19 outbreak on students in a French region severely affected by the disease: results of the PIMS-CoV 19 study. (January 2021) - Bourion-Bédès, Stéphanie; Tarquinio, Cyril; Batt, Martine; Tarquinio, Pascale; Lebreuilly, Romain; Sorsana, Christine; Legrand, Karine; Rousseau, Hélène; Baumann, Cédric
Highlights: Compared to previous studies in China, greater levels of anxiety were reported among French students in an area particularly affected by the disease, with more than half of these students experiencing anxiety. Female gender and having relatives or acquaintances from their residence hospitalized for COVID-19 were the main risk factors for moderate to severe anxiety. Support from family and support from friends were protective factors against anxiety. Abstract: The COVID-19 has sent billions of students worldwide into lockdown. The study aimed to assess the prevalence of anxiety and identify the factors associated with anxiety among French students during lockdown.A cross-sectional study was conducted to collect sociodemographic data, living and learning conditions, anxiety symptoms and social support. Among 3936 students, 15.2%, experienced moderate anxiety and 9.8%, severe anxiety.Female gender (OR=2.2, 95% CI: 1.8-2.7) and having relatives or acquaintances from their housing hospitalized for COVID-19 (OR=3.3, 95% CI: 1.4-7.9) were the main risk factors for anxiety. Tensions at home (OR=1.8, 95% CI: 1.5-2.1), difficulties isolating (OR=1.4, 95% CI: 1.1-1.6), noises inside (OR=1.6, 95% CI: 1.3-1.9) or outside the housing (OR=1.5, 95% CI: 1.3-1.8), no direct outdoor access (OR=1.6, 95% CI: 1.3-2.0), delay in final examination (OR=1.6, 95% CI: 1.3-2.1), reduced time for learning (OR=1.3, 95% CI: 1.1-1.6), increased tobacco consumption (OR=1.9, 95% CI: 1.4-2.6), ineffectiveness of using media entertainment (OR=2.2, 95% CI: 1.1-4.4) and reading (OR=1.9, 95% CI: 1.3-2.7) to calm down, were identified as risk factors. Family (OR=0.85, 95% CI: 0.8-0.91) and friend (OR=0.88, 95% CI: 0.82-0.94) support were protective factors. This suggests the need to focus on students during epidemics, especially those living with someone hospitalized with COVID-19.